2020
DOI: 10.1177/0261927x20949594
|View full text |Cite
|
Sign up to set email alerts
|

The Deception Spiral: Corporate Obfuscation Leads to Perceptions of Immorality and Cheating Behavior

Abstract: In four studies, we evaluated how corporate misconduct relates to language patterns, perceptions of immorality, and unethical behavior. First, we analyzed nearly 190 codes of conduct from S&P 500 manufacturing companies and observed that corporations with ethics infractions had more linguistically obfuscated codes than corporations without ethics infractions. Next, we tested perceptions of a company based on values statements modified by obfuscation (Study 2). Participants perceived low-obfuscation compani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 49 publications
1
25
0
Order By: Relevance
“…This investigation sought to determine the broad influence of language complexity on behavior. Indeed, an abundance of research studies obtained in the laboratory and through experiments have revealed the consistent influence of language complexity on judgments and decision making through processing fluency (5,(13)(14)(15). Despite this consensus, what has been less understood is whether people are actually compelled by the heuristic of language complexity in daily life and within settings of consequence (e.g., when ideas or money are exchanged).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This investigation sought to determine the broad influence of language complexity on behavior. Indeed, an abundance of research studies obtained in the laboratory and through experiments have revealed the consistent influence of language complexity on judgments and decision making through processing fluency (5,(13)(14)(15). Despite this consensus, what has been less understood is whether people are actually compelled by the heuristic of language complexity in daily life and within settings of consequence (e.g., when ideas or money are exchanged).…”
Section: Discussionmentioning
confidence: 99%
“…Writers of personal admissions statements to college were perceived as less intelligent if their essay contained complex words compared to simple words. Other work suggests companies that contain high rates of jargon in their values statements tend to be viewed as less moral, less warm, and less trustworthy than companies with low rates of jargon (13). This general effect has been replicated in many studies, where people form more positive perceptions of a target when simple versus complex language is used (5,(13)(14)(15).…”
Section: Lexical Fluency and Metacognitive Processingmentioning
confidence: 90%
See 1 more Smart Citation
“…The procedure for this study closely followed prior research (Markowitz, Kouchaki, et al, 2021) and included key measures from prior work as well (Serota & Levine, 2015;Serota et al, 2010).…”
Section: Procedures and Measuresmentioning
confidence: 99%
“…Verbal complexity was evaluated with the same four language markers from prior work (Markowitz, 2019): word count (e.g., the raw number of words in each abstract), 1 words per sentence (e.g., the number of words in each sentence per abstract), the rate of common words in English, and the rate of analytic thinking. Consistent with prior studies (Markowitz, 2019;Markowitz & Hancock, 2016;Markowitz et al, 2021), the rate of common words was operationalized by the LIWC dictionary category. Words outside of the LIWC dictionary are considered jargon, technical language, and specialized terms (Tausczik & Pennebaker, 2010).…”
Section: Complexity Measuresmentioning
confidence: 99%